Overview of the PMBOK® guide paving the way for PMP® certification - Ó Conchúir, Deasún (Springer Berlin Heidelberg Imprint: Springer, 2012)
This book is a valuable resource as it provides an introduction to project management's generally recognized good practices as described in A Guide to the Project Management Body of Knowledge (PMBOK® Guide)- Fourth Edition, published by Project Management Institute (PMI), the world's leading association for the project management profession. Style and language make Overview of the PMBOK® Guide especially useful for individuals who speak English as a foreign language and are preparing for PMI's certifications, particularly the Certified Associate in Project Management (CAPM®) and the Project Management Professional (PMP®). The CAPM demonstrates an understanding of the principles and terminology of the PMBOK® Guide. The PMP demonstrates experience, education and competency to successfully lead and direct projects. The PMBOK® Guide is a foundational resource for all PMI certifications.